Revisão taxonômica e análise filogenética das espécies do gênero neotropical Balacha Melichar (Insecta, Hemiptera, Cicadellidae, Cicadellinae) - Takiya, Daniela Maeda (2001)
Redescription of the genus Balacha Melichar and also redescriptions and illustrations of its six recognized species are provided: B. decorata Cavichioli & Sakakibara, B. distincta (Signoret), B. lepida Cavichioli & Sakakibara, B. melanocephala (Signoret) (type-species), B. rubripennis Cavichioli & Sakakibara, and B. similis Cavichioli & Sakakibara. In the redescriptions are included new morphological characters, specially those of the fmale genitalia. The interai abdominal stemite VII was observed fr the frst time in B. distincta, B. rubripennis and Pawiloma ancora Young. A neotype fr B. melanocephala is elected, considering the type specimen is probably lost. The geographical distribution of the species of the genus is reviewed, including new records of B. decorata (Brazil: Minas Gerais State), B. distincta (Brazil: São Paulo State), B. melanocephala (Uruguay and Argentina) and B. simils (Brazil: Minas Gerais and Rio de Janeiro states). Previous records fom Colombia of B. distincta and B. melanocephala are taken as erroneous. A key to species based on male and fmale specimens of Balacha is also provided. A cladistic analysis of the known species of Balacha and eleven related outgroup taxa, based on 64 morphological characters, corroborates the hypothesis of monophyly of the genus and its sister group relationship to Pegogonia Young.